2022
DOI: 10.4155/bio-2022-0024
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Dendritic Cell Antibody Internalization as an Immunogenicity Risk Assessment Tool

Abstract: Aim: Immunogenicity risk assessment assays are powerful tools that assess the relative immunogenicity of potential biotherapeutics. We detail here the development of a novel assay that measures the degree of antibody internalization by antigen-presenting cells as a predictor of immunogenicity. Results & methodology: The assay uses the fluorescence signal from the antibody bound to the outside of the cell as well as inside the cell to determine internalization. To calculate the amount of internalized antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…As a first ex vivo experimental assessment of immunogenicity risk, we used a previously reported DC internalization assay. 36 This assay was used to recapitulate an early step in ADA generation, namely, internalization of the protein therapeutic by APCs such as DCs. Previous studies revealed a correlation between a DC internalization index and an increased risk of immunogenicity in a panel of tested antibodies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a first ex vivo experimental assessment of immunogenicity risk, we used a previously reported DC internalization assay. 36 This assay was used to recapitulate an early step in ADA generation, namely, internalization of the protein therapeutic by APCs such as DCs. Previous studies revealed a correlation between a DC internalization index and an increased risk of immunogenicity in a panel of tested antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…Several different computational and experimental methods were used to assess the immunogenicity risk of the monospecific and bispecific antibody panel related to specific steps in the pathway of antigen-processing through to ADA generation by plasma cells ( Figure 1 ). The three steps and selected assays are as follows: 1) antigen-presenting cells (APCs) such as dendritic cells (DCs) process the protein therapeutic, which can be interrogated by a DC internalization assay, 36 2) APCs present the processed peptides through class II major histocompatibility complex (MHC-II), which can be modeled by in silico prediction of peptide presentation by MHC-II 37 and experimentally evaluated by MHC-associated peptide proteomics (MAPPs), 38 , 39 and 3) the MHC-II complex recruits and activates T cells, which can be assessed by ex vivo methods such as T cell activation 40 or proliferation. 41
Figure 1.
…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of antibody internalization in antigen-presenting DCs has been proposed as a tool for immunogenicity risk assessment because a higher degree of internalization generally correlates with higher clinical immunogenicity. 36 However, in a similar assay, the internalization rate of these compounds in murine DC revealed no simple correlation with their corresponding immunogenic potential in hIgG1 transgenic mice. Finally, the artificial mixture of CEA-IgG with soluble IL2v or a one-armed antibody specific for mCD3ε confirmed T cell activation as the mechanism causing the ADA responses of CEA-IL2v and CEA-mTCB, respectively ( Figure 4 and Figure 5 and Supplementary Figure 5).…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, the propensity of mAbs to be internalized in vitro by APCs, particularly DCs, which are the most potent APCs, is a valuable assay of potential immunogenicity [ 108 ]. Two strategies have been used: either direct conjugation of a fluorescent dye to the protein therapeutic or indirect detection with a secondary, often fluorescently labeled, molecule [ 109 ]. Each has advantages and disadvantages.…”
Section: In Vitro Approaches To Predicting Immunogenicitymentioning
confidence: 99%